(untitled) (The Research of Medical Science Review, 2025)
Background: The prevalence of diabetes mellitus is rising worldwide, especially among women, making it a serious public health concern. Among District Mardan, Pakistan, this study sought to ascertain the prevalence of diabetes mellitus and identify risk variables among females. Method: In District Mardan, 150 randomly chosen female participants participated in a cross-sectional study. A standardized questionnaire covering demographics, anthropometric measurements (Body Mass Index, or BMI), self-reported levels of physical activity, stress, residential area, and personal and family history of diabetes was used to gather data. Using SPSS version 22, statistical analysis was conducted to determine the prevalence of diabetes and the relationship between possible risk variables and diabetes status. Results: It was discovered that 59.3% (n=89) of the study sample had diabetes mellitus. Significant correlations between diabetes and a number of risk variables have been found through statistical research. Compared to participants without diabetes, those with diabetes had a considerably higher mean BMI and a higher percentage of those who were overweight (33.7%) and obese (38.2%).Diabetes became more common as people aged, with women over 40 having the highest prevalence (81.3%). Lastly, the diabetes group had a considerably higher prevalence of high stress levels (46.0%) than the non-diabetic group (21.3%). Conclusion: A high prevalence of 59.3% was found in this study, which examined the risk factors and prevalence of diabetes mellitus in 150 women from District Mardan, Pakistan. Diabetes was found to be significantly correlated with greater BMI, less physical activity, aging (particularly over 40), living in an urban area, and higher levels of stress